Report of the meeting of the Ad Hoc Expert Group on Fertilizer Production in Six Selected Countries with Good Natural Gas Resources - United Nations Industrial Development Organization (New York : United Nations, 1969)
This report entails a meeting of the Ad Hoc expert group on fertilizer production organized by the Centre for Industrial Development of the United Nations to examine the possibilities of large-scale production of fertilizers using natural gas in six selected countries, namely, Iran, Kuwait, Libya, Nigeria, Saudi Arabia, and Venezuela.
Cover title: Fertilizer production in six selected countries with good natural gas resources.
"United Nations publication. Sales no.: E 69. II. B. 5."
Includes bibliographical references: p. 57-58.
ne 12/04/2019
Ref
Keywords: Fertilizer industry; Natural gas